1998
DOI: 10.1161/01.cir.98.9.839
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Pravastatin, and the Risk of Coronary Events After Myocardial Infarction in Patients With Average Cholesterol Levels

Abstract: Evidence of inflammation after MI is associated with increased risk of recurrent coronary events. Therapy with pravastatin may decrease this risk, an observation consistent with a nonlipid effect of this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
675
8
31

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,228 publications
(750 citation statements)
references
References 31 publications
36
675
8
31
Order By: Relevance
“…It extends recent observations in which composite or nonfatal endpoints were utilized 10 by showing that, in this population, CRP predicts the single hard endpoint of overall mortality. The reasons that high CRP levels predict death are probably twofold.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…It extends recent observations in which composite or nonfatal endpoints were utilized 10 by showing that, in this population, CRP predicts the single hard endpoint of overall mortality. The reasons that high CRP levels predict death are probably twofold.…”
Section: Discussionsupporting
confidence: 80%
“…9 The reasons that the reduction of CRP levels caused by simvastatin did not translate into a reduction of the risk of mortality in patients with higher CRP levels at baseline cannot be ascertained by the results of our study. Of note, in a case-control study, Ridker et al compared prerandomization serum CRP levels in 391 patients with previous MI enrolled in the CARE trial, who had cardiac events, and in matched controls; 10 the authors found that the beneficial effects of treatment with pravastatin were predominantly present in patients with raised CRP levels at baseline. More recently, in a trial of primary prevention, Ridker et al found a beneficial effect of lovastatin treatment in patients with high CRP levels even in the absence of hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-sensitivity C-reactive protein (CRP), a marker of inflammation, has been identified as an independent predictor of adverse cardiac events in healthy populations and in patients with stable coronary artery disease or ACS (6)(7)(8)(9)(10)(11). Although it is clear that inflammation plays a role in atherosclerotic complications (12), the relationship between CRP and troponin release following PCI has not been clarified.…”
mentioning
confidence: 99%
“…Data from the Cholesterol and Recurrent Events trial indicated that long-term statin therapy lowered plasma levels of CRP, and the efficacy in lowering the event rate was greatest in those with increased levels of CRP [88]. This effect was also seen in other studies and might be independent of LDL cholesterol [89,90].…”
Section: Lowering Of Inflammatory Markers Might Decrease Cardiovasculmentioning
confidence: 64%